Evaluation of the Islamic Boarding School Empowerment Program in East Java Province - Maya Puspita Dewi; Muh Barid Nizarudin Wajdi (Al-Hayat Al-Istiqomah Foundation collab with Letiges, 2022)
The purpose of this study is to evaluate the efforts of the East Java Provincial Government in empowering Islamic Boarding Schools, with a specific focus on their roles as educational and religious institutions, by Law No. 18 of 2019 on Islamic Boarding School. This study adopts a qualitative research approach guided by Peter H. Rossi's Program Evaluation Theory. Data collection methods encompass in-depth interviews with key stakeholders, including government officials, Islamic Boarding School leaders, educators, and community members. Additionally, policy document analysis and direct observations within Islamic Boarding School institutions. The collected data is transcribed and thematically analyzed, guided by Program Evaluation Theory by content analysis. The findings reveal significant advancements in the empowerment of Islamic boarding schools by the East Java Provincial Government. These improvements encompass increased accessibility, elevated educational quality, and economic empowerment within the Islamic Boarding School system. Notable measures contributing to these enhancements include teacher training, the development of inclusive curricula, and improved financial support. Law No. 18 of 2019 serves as a robust legal framework underpinning the empowerment of Islamic Boarding Schools. Nevertheless, challenges persist, including resource limitations, restricted stakeholder cooperation, and the imperative for more effective monitoring and evaluation mechanisms. This research contributes valuable insights into evaluating Islamic Boarding School empowerment programs within the context of Law No. 18 of 2019. It employs the Program Evaluation Theory as a robust framework for assessment. The findings emphasize the value of policy support and collaboration to sustain and improve Islamic Boarding School empowerment in East Java.